Some reactions to paradigmatic behaviorism's theory of intelligence - Cone, John D. (Psicothema, 1989)
In "Paradigmatic behaviorism's theory of intelligence: A third-generation approach to cognition", Arthur STAATS provides a brief, albeit informative overview of his third generation behavioral conception of intelligence and other complex verbal (cognitive) phenomena. It is an interesting, eminently readable account of paradigmatic behaviorism's contributions in these areas.